Summaries of cases visited by the almoner - Cornish, F.
1901-12-30 1901 1900s 6 pages re Hall — Christine — 8 months Dec 30th 1901 8a/1902 1902 Visited 112 Morley Avenue saw Mrs. Hall who said her husband worked at Kings Cross for Carter Pattison and earned 24/- a week The family consisted of man and wife and 7 children, the eldest a girl of 16 had been at service but not being strong had had to come home about 6 weeks ago, and has earned nothing since. Mrs. H does not consider this much of a loss as the girl looks after the children which enables Mrs. Hall to do a little charing and washing by which she earns 2/- or 3/- a week. Mrs. Hall stated the whole of the children had attended the Hospital at various times. The family occupy a small house of 4 rooms for which the rent is 8/9 a week which was paid up to date. Mrs Hall gave as a reference Mrs Long of 42 Cranbrook Park who said she had known Mrs Hall for a number of years as a hardworking respectable person, Mrs. Long used to employ her 2 days a week washing and charing but owing to Mrs. Hall's family being so large and sickly she has had as much as she could do at home. eczema [ ] Hosp case Rowley — Herbert 8 10360 Visited Mrs Rowley of Brampton Rd. who said her husband was a carpenter but on being informed of the object of the visit would give no information as to his wages &c. Mrs Rowly said the boy Herbert had been taken to the Hospital about 3 weeks ago by another person to be examined, but she did not know what was said except that there would have to be an operation. Mrs. Rowley seemed to be under the impression this could be done at the Hospital gratis and said afterwards they would probably have it done by a private doctor. On inquiries from the neighbours I gathered the information that the house (which was a large one) belonged to Mr. Rowley and that it was reported that he owned 3 or 4 more round the neighbourhood which I believe is quite correct although I could not find where they were situated. Report No information [ ] 378/IMSW/A/1/6/8a